A bibliometric analysis of fuel subsidy: a call for action / Juliana Mohamed Abdul Kadir ... [et al.] - Abdul Kadir, Juliana Mohamed; Ismail, Norashikin; Ramli, Ahmad Razi; Othman, Akmal Aini; Mhd Noh, Nor Aziedah; Govindaraju, Chandran (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
Fuel subsidies play a vital role in mitigating inflation and lowering fuel production expenses, particularly during periods of surging global crude oil prices. The study's objectives involve a comprehensive assessment, mapping research studies to understand current trends, publication impact, research productivity in fuel subsidy studies, and identifying the most influential countries, institutions, and authors in this field. This research conducts a bibliometric analysis of fuel subsidies and their trends, utilizing data and academic literature from the Scopus database retrieved on October 4, 2022, with the keywords "fuel" and "subsidy" in the title string. Examining 168 articles spanning 1978 to 2022, quantitative data analysis employed Microsoft Excel, VOSviewer, and Harzing's Publish or Perish. Results reveal a rising trend in article publication since 2014, peaking at 23 articles in 2017. The United States (USA), the United Kingdom (UK), and China emerge as the most productive countries in fuel subsidy studies, with the USA playing a crucial role in international collaboration. The most cited paper garnered 164 citations. Future research is encouraged to explore broader areas, linking fuel subsidies with low carbon societies, environmental policy, renewable energy, or the blue economy, given their global significance. The study's findings aim to guide researchers in planning future investigations, offering relevant literature and critical issues to address, ultimately enhancing the quality of knowledge in this domain.